An Investigation of Insect Ovipositing Repellent Activity of Andrographis paniculata Ness, Acacia auriculiformis and Piper betle Linn Leaves Extracts to Batrocera carambolae - Nurcahyo Iman Prakoso; Umul Azizah; Zahrah Nur Zakiyah; Mila Tria Nita; Arida Liyanita; Suputa Suputa (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2018)
Batrocera carambolae was one of the main pests in some types of fruits. This pest attack resulted in quantitative damage in the form of fall of young fruit and qualitatively in the form of fruit to rot and contains maggots. This research was conducted to determine selected extract from Andrographis Paniculata Ness, Piper betle Linn and Acacia auriculiformis leaves which have repellent activity for Batrocera carambolae. Nine extracts from the maceration process of the three leaves were evaluated by placing the extracts and flies together in the cage. The ethanol, ethyl acetate, and n-hexane extracts from Andrographis Paniculata Ness, Piper betle Linn and Acacia auriculiformis leaves were applied to the test pieces and fed into a cage containing 10 male and female flies. From observation, N-hexane extracts from Andrographis Paniculata Ness and Piper betle Linn leaves and ethyl acetate extracts from Acacia auriculiformis leaf Â having good activity as repellent and potentially to be used as a insect ovipositing repellent of Batrocera carambolae.